2004
DOI: 10.1093/brain/awh277
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical dysplasias: surgical outcome in 67 patients in relation to histological subtypes and dual pathology

Abstract: The purpose of this study was to assess whether the histological subtype of focal cortical dysplasia and dual pathology affect surgical outcome in patients with medically intractable epilepsy due to focal cortical dysplasia (FCD). We retrospectively analysed the outcome of 67 patients from 2 to 66 years of age at follow-up periods of 6 to 48 months after epilepsy surgery. Histological subtypes were classified according to Palmini and included a few cases with mild histological abnormalities corresponding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
166
1
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(187 citation statements)
references
References 39 publications
5
166
1
15
Order By: Relevance
“…5,14,19,21,28,31,32 Some studies, however, have shown better outcomes for patients with Type I CD, 5,8 and other studies have shown no difference in outcome between patients with milder and those with more severe CD subtypes. 13 The few studies specifically evaluating children are less conclusive.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…5,14,19,21,28,31,32 Some studies, however, have shown better outcomes for patients with Type I CD, 5,8 and other studies have shown no difference in outcome between patients with milder and those with more severe CD subtypes. 13 The few studies specifically evaluating children are less conclusive.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Several clinical research groups have studied the impact of different radiological or clinicopathological factors on seizure outcome after extirpative surgery for FCD. [4][5][6][7][8][9][11][12][13][14][15]23,24,26,28,29 Recently, Rowland et al 22 reported on their meta-analysis of predictors of seizure freedom in the surgical management of FCD on the basis of results from 37 selected studies. They noted that complete resection of the anatomical or electrographic abnormality was the most important treatment-related factor predictive of seizure freedom.…”
mentioning
confidence: 99%
“…[7][8][9][10] In a subset of these tumors, which are generally low-grade glial or glioneuronal neoplasms, multiple pathologies, which potentially may contribute to the genesis of these seizures, are identifiable (dual pathology). [11][12][13][14][15][16] Among these, there is a well-established association of certain neoplasms with malformations of cortical development (cortical dysplasia), particularly dysembryoplastic neuroepithelial tumors and gangliogliomas. [17][18][19][20] The purpose of this study is to systematically review one institution's experience with neoplasms associated with identifiable coexistent pathology arising in the setting of chronic epilepsy.…”
mentioning
confidence: 99%